AVALIAÇÃO DAS ALTERAÇÕES DENTÁRIAS E ESQUELÉTICAS APÓS A DISTALIZAÇÃO DE MOLARES SUPERIORES COM APARELHO PÊNDULO SOB A INFLUÊNCIA DO LASER DE BAIXA INTENSIDADE - Francio, Fabíola (2012)
This study evaluated the rate of orthodontic movement, and dental/skeletal effects in distalization of maxillary molars under the influence of low intensity laser using cephalometric radiographs. The sample was composed of 18 patients with Class II malocclusion, initial mean aged of 14,4 years and divided into two groups: Group I - laser and Group II - control. Patients were treated with modified Hilgers Pendulum orthodontic appliance, at the same time low intensity laser was applied to the right and left sides, to the root region of the first and second molars; in nine patients of the sample; by the protocol: 780nm wavelength, 40mW power, 10J/cm² energy density, 0.4J power for 10 seconds per point an each point resulting in a total energy of 20.8J. Fifty-two points were distributed in the buccal and palatal side of the first and second upper molars. Laser treatment was performed on the activation of TMA spring and repeated every month until over correction of molar ratio. The lateral radiographs were done at initiation of treatment (T1), at final of third month (T2) and at the end of molar distalization (T3) with over correction by approximately 1mm. Cephalometric analyses were done to compare the initial (T1) and final (T3) stage and Initial (T1) and third month (T2) stage and to compare between groups. The results showed distal tipping of the first and second molars, buccal inclination of the upper central incisors accentuated by the presence of the second molars and absence of significant vertical dental changes. The mandibular plane moved clockwise, consequently increasing lower anterior facial height. It was concluded that the changes introduced by modified Hilgers Pendulum appliance were predominantly dento alveolar and the effect of laser therapy did not show significant statistically difference in the speed of orthodontic tooth movement of the first and second molars and, neither, on the variables studied.